Influence of defect states on the performances of planar tin halide perovskite solar cells. (March 2019) - Huang, Shihua; Rui, Zhe; Chi, Dan; Bao, Daxin
Abstract: Although tin halide perovskite has shown excellent photoelectric performance, its efficiency of solar cell is low compared with that of lead halide. In order to enhance the efficiency of tin halide perovskite solar cell, a deep understanding of the role of the defects in the perovskite absorption layer and at the electron transport layer (ETL)/absorber or absorber/hole transport layer (HTL) interface is very necessary. In this work, the planar heterojunction-based CH3 NH3 SnI3 perovskite solar cells were simulated with the SCAPS-1D program. Simulation results revealed a great dependence of device efficiency on defect density and interface quality of the perovskite absorber. The defect density at the front interface is critical for high efficiency, and the polarity of the interface charge has a different impact on the device efficiency. Strikingly, an efficiency over 29% was obtained under the moderate simulation conditions.